MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS PROSEDUR KOMPLEKS DI SMK - Kamaria Kamaria; Herman Budiyono; Ade Kusmana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Project-based learning guides students through systematic and standardized work procedures to make or complete a product through the actual production process. This study aims to improve the quality of learning outcomes to write complex procedure texts by applying a project-based learning model. This type of research is classroom action research and consists of two cycles. The research process includes planning, implementation, action, observation and reflection. The subjects of this study were students of SMK Negeri 1 Tanjung Jabung Timur, totaling 17 students. The results showed that students achieved 68% learning outcomes in cycle I and 88% learning outcomes in cycle II. This study concludes that the use of project-based models improves the quality of learning outcomes in writing complex procedural texts at SMK Negeri 1 Tanjungjabung Timur